Re: Instruction regarding VO#19 rain chain & cut-off ditch work - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the instruction regarding variation order of rain chain & cut-off ditch work for BRACU new campus project.